Carbon structure

By using a three-dimensional carbon structure with petal-shaped and concave-convex structure, combined with a graphene skeleton and carbon binder, the problems of poor forming and insufficient durability of nanodiamonds are solved, and the high intensity of cold neutrons and durability in high radiation fields are achieved.

CN119894819APending Publication Date: 2025-04-25INCUBATION ALLIANCE +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380067536.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-06
Filing Date
2023-09-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When nanodiamond is a neutron reflective material, due to poor forming properties, it is difficult to obtain a structure that maintains a sufficient thickness and volume along the speed reduction material or the neutron extraction surface, and the durability is insufficient in a high radiation field.

Method used

A three-dimensional shaped carbon structure with a petal-like structure and a concave-convex structure is used to form a nanocarbon structure through a combination of a graphene skeleton and a carbon binder to improve formability and durability.

Benefits of technology

The high intensity of cold neutrons or ultra-cold neutrons is achieved, the durability in high radiation fields is improved, and the good formability of the material is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894819A_ABST
    Figure CN119894819A_ABST
Patent Text Reader

Abstract

Provided is a three-dimensionally shaped carbon structure including a nanocarbon structure having at least one of a petal-shaped structure in which flake-shaped carbon having a graphene skeleton and a thickness of less than 20 nm is fixed in a petal shape and a concavo-convex structure in which the thickness of the flake-shaped carbon is less than 20 nm. And the concave-convex structure is formed by aggregating seed-shaped structural bodies with the size of 1-100 nm. The carbon structure has good moldability and excellent durability in a high radiation field, and can increase the strength of cold neutrons or ultra-cold neutrons by coherent scattering, and thus is suitable as a reflective material for cold neutrons or ultra-cold neutrons.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon structure. More specifically, it relates to a three-dimensional carbon structure that can increase the intensity of cold neutrons or ultracold neutrons by coherent scattering, and the cold neutrons or ultracold neutrons are expected to be effectively applied to a wide range of fields such as structural analysis of materials, life sciences, and medicine. Background Art

[0002] Cold neutrons (0.1 to 5 meV) have a long wavelength and are suitable for studying the structure of matter. Their application in the field of structural analysis of high-temperature superconductors and biomaterials is developing. In addition, ultracold neutrons (0.5 μeV to less than 0.1 meV) are used to study the effects of the four forces existing in nature.

[0003] Nanodiamond (ND) has attracted attention as a material that increases the strength of neutrons including cold neutrons (Non-Patent Document 1).

[0004] Prior art literature

[0005] Non-patent literature

[0006] Non-patent literature 1: M. Teshigawara, et al., Nuclear Inst. and Method in Physics Research, A 929 (2019) 113-120 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, when nanodiamond is used as a neutron reflector, it is difficult to obtain a structure that maintains sufficient thickness and volume along the moderator or neutron extraction surface due to its poor formability. In addition, the neutron reflector is also required to have durability in high radiation fields.

[0009] The present invention provides a reflective material for cold neutrons or ultracold neutrons, which has good formability, can increase the intensity of cold neutrons or ultracold neutrons by coherent scattering, and can also be expected to have durability in high radiation fields.

[0010] Means for solving problems

[0011] The inventors of the present invention conducted in-depth research to solve the above-mentioned problems, and found that if a three-dimensional carbon structure having at least one of a petal-like structure (which is formed by fixing thin flaky carbon with a graphene skeleton less than a predetermined thickness into a petal shape) and a concave-convex structure (which is formed by agglomerating seed-like structures of a predetermined size) is used, the above-mentioned problems can be solved. The inventors of the present invention further conducted repeated research and completed the present invention.

[0012] That is, the present invention relates to a carbon structure, which is a three-dimensional carbon structure including a nanocarbon structure, wherein the nanocarbon structure has at least one of a petal-like structure and a concave-convex structure, wherein the petal-like structure is formed by fixing thin flake carbon with a thickness of less than 20 nm having a graphene skeleton into a petal shape, and the concave-convex structure is formed by the aggregation of seed-like structures with a size of 1 to 100 nm.

[0013] Effects of the Invention

[0014] According to the present invention, a cold neutron or ultracold neutron reflector can be provided, which has good formability, can increase the intensity of cold neutrons or ultracold neutrons by coherent scattering, and can also be expected to have durability in high radiation fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram showing the structure of a muffle furnace.

[0016] Figure 2 is a SEM image of the nanocarbon structure 1.

[0017] Figure 3 is a SEM image of the nanocarbon structure 1.

[0018] Figure 4 is a SEM image of the nanocarbon structure 2.

[0019] Figure 5 is a SEM image of the nanocarbon structure 2.

[0020] Figure 6 is a SEM image of the nanocarbon structure 2.

[0021] Figure 7 is a SEM image of the nanocarbon structure 2.

[0022] Figure 8 is a SEM image of the nanocarbon structure 2.

[0023] Fig. 9 is a SEM image of the nanocarbon structure 2.

[0024] Fig.10 is a SEM image of the nanocarbon structure 2.

[0025] Fig.11 is a SEM image of the nanocarbon structure 2.

[0026] Fig.12 is a SEM image of the nanocarbon structure 2.

[0027] Fig.13 is a SEM image of thermally expanded graphite.

[0028] Fig.14 It is a SEM image of graphene aggregate.

[0029] Fig.15 This is a photograph of a three-dimensional carbon structure 3.

[0030] Fig.16 This is a photograph of a three-dimensional carbon structure 4.

[0031] Fig.17 This is a photograph of a three-dimensional carbon structure 5.

[0032] Fig.18 This is a photograph of a three-dimensional carbon structure 6.

[0033] Fig.19 This is a photograph of a three-dimensional carbon structure 7.

[0034] Fig. 20 This is a SEM image of the three-dimensional carbon structure 4.

[0035] Fig.21 This is a SEM image of the three-dimensional carbon structure 6.

[0036] Fig. 22 This is a SEM image of the three-dimensional carbon structure 7.

[0037] Fig.23 This is a SEM image of the three-dimensional carbon structure 7.

[0038] Fig.24 This is a SEM image of the three-dimensional carbon structure 7.

[0039] Fig.25 This is a SEM image of the three-dimensional carbon structure 7.

[0040] Fig.26 It is a schematic diagram showing an example of the shape of a three-dimensional carbon structure.

[0041] Fig. 27 This is a graph that plots the neutron transmittance as a function of the energy of each sample used in the test. DETAILED DESCRIPTION

[0042] Hereinafter, the three-dimensional carbon structure of the present invention, i.e., the three-dimensional carbon structure including the nanocarbon structure, is described. Here, the nanocarbon structure has at least one of a petal-like structure and a concave-convex structure, wherein the petal-like structure is formed by fixing a thin sheet of carbon having a graphene skeleton and a thickness of less than 20 nm into a petal-like shape, and the concave-convex structure is formed by aggregating seed-like structures of 1 to 100 nm in size.

[0043] Although not wishing to be bound by theory, the reasons why the three-dimensional carbon structure of the present invention has good formability, can increase the intensity of cold neutrons or ultracold neutrons by coherent scattering, and can be expected to have durability in high radiation fields are as follows.

[0044] The three-dimensional carbon structure of the present invention comprises a nano carbon structure having at least one of a petal-shaped structure and a concave-convex structure, wherein the petal-shaped structure is formed by fixing a thin sheet of carbon having a graphene skeleton with a thickness of less than 20 nm into a petal-shaped structure, and the concave-convex structure is formed by aggregating seed-shaped structures of 1 to 100 nm in size. This nano-sized fine structure is considered to be a size suitable for interacting with the wavelength of cold neutrons or ultracold neutrons, and is therefore considered to be the cause of coherent scattering of cold neutrons or ultracold neutrons.

[0045] In addition, with regard to the manufacture process of the three-dimensional shape carbon structure in this specification, in the process of obtaining the three-dimensional shape structure, use graphene aggregate etc. as carbon binder, and the mixture that this carbon binder is mixed with nano carbon structure is compression molded.In this case, the strong van der Waals force that the graphene of this carbon binder causes is bonded to nano carbon structure each other, on the other hand, because this carbon binder itself is the carbon material of the nanometer size with graphene, therefore think that the influence that the petaloid structure, the concavo-convex structure failure of nano carbon structure can be suppressed to minimum, formability is provided.It should be noted that, with regard to the constituent element of the present invention, carbon binder is not indispensable, therefore for example when nano carbon structure itself is used as the three-dimensional shape carbon structure of the present invention, carbon binder is not needed.

[0046] Furthermore, since the three-dimensional carbon structure of the present invention is composed of a carbon material with graphene having high crystal structure strength as a skeleton, it is believed that it has excellent durability in a high radiation field. That is, the graphite structure involved in the graphene skeleton is formed by sp2 carbon bonds, and the electrons not involved in the sp2 carbon bonds exist in a non-localized state. Compared with the sp3 carbon bonds of diamond, etc., the presence of the non-localized electrons is more conducive to the durability in a high radiation field.

[0047] <Definition>

[0048] "The thickness of the carbon structure" refers to: under three mutually orthogonal coordinate axes (x-axis, y-axis, z-axis) in three-dimensional space, when the major axis direction of the carbon structure is set to the x-axis direction and the minor axis direction of the carbon structure is set to the y-axis direction, the length of the z-axis direction of the carbon structure is the thickness. However, the lengths of "major axis", "minor axis" and "thickness" are in the order of major axis>minor axis>thickness. It should be noted that when it is difficult to distinguish the thickness of the carbon structure under the above method, the thickness of the carbon structure refers to: when the maximum diameter of the carbon structure is taken as the major axis, and the maximum diameter of the carbon structure in the direction perpendicular to the above major axis is taken as the minor axis, the maximum diameter of the carbon structure in the direction perpendicular to both the above major axis and the above minor axis.

[0049] The “tapped density” refers to the density measured on a powder. The method of measuring the density is, for example, to collect the powder (thermal expansion graphite, etc.) to a volume of 100 cm 3 The weight of the powder is obtained by dividing the value by 100 cm. 3 , thus obtaining the measured value.

[0050] Bulk density is the mass per unit volume (g / cm2) calculated by dividing the volume calculated from the external dimensions (shape) by the measured mass. 3 ).

[0051] The “G band” refers to the band that appears at 1580 cm in the Raman spectrum of graphene. -1 One of the characteristic peaks near 1580cm, which is derived from the stacking structure of graphene. The more regular the stacking structure of graphene, the higher this peak tends to be. -1 Nearby means ±100cm is allowed -1 displacement.

[0052] The “D band” refers to the band that appears at 1360 cm in the Raman spectrum of graphene. -1 One of the characteristic peaks near 1360cm, which is derived from the disorder and defects of the stacked structure of graphene. As the disorder and defects increase, the peak tends to become higher. -1 Nearby means ±100cm is allowed -1 displacement.

[0053] The “2D band” refers to the band that appears at 2700 cm in the Raman spectrum of graphene. -1One of the characteristic peaks near 2700cm, which is correlated with the number of graphene layers. As the number of layers decreases, the peak tends to become higher. The peak of the 2D band is at 2700cm -1 Nearby means ±100cm is allowed -1 displacement.

[0054] "Nanocarbon structure" is a carbon material having at least one of a petal-like structure and a concave-convex structure, wherein the petal-like structure is formed by fixing a flaky carbon having a graphene skeleton and a thickness of less than 20nm into a petal-like shape, and the concave-convex structure is formed by aggregating seed-like structures of 1 to 100nm in size. The petal-like structure and the concave-convex structure will be described later. The thickness of the flaky carbon can be less than 15nm or less than 10nm.

[0055] The “carbon binder” refers to a carbon material used as a binder for forming a nanocarbon structure.

[0056] "Thermal expansion graphite" refers to graphite particles formed by overlapping carbon hexagonal meshes that expand several hundred times in the thickness direction. It can be produced by rapidly heating a graphite intercalation compound.

[0057] "Graphene aggregate" refers to an aggregate of graphene formed by the accumulation of single or multiple layers of graphene. It should be noted that in this specification, "graphene" may refer not only to a single layer structure, but also to a multilayer structure. Here, for graphene, multilayers preferably have a thickness of less than 100 nm and a number of layers of 290 or less. The number of layers may also be, for example, less than 200 layers, or less than 100 layers, or less than 50 layers, or less than 25 layers.

[0058] The particle size of the graphene aggregate includes: the particle size of the primary particles in the state of being dispersed in the liquid (primary particle size); and the particle size (secondary particle size) of the crushed body of the primary particle deposit obtained by separating the liquid from the dispersed state by filtration, drying and crushing. The primary particle size is preferably less than 100 μm, more preferably less than 50 μm, and further preferably less than 10 μm. In addition, the secondary particle size also depends on the shape of the formed nanocarbon structure, and is generally preferably less than 1 mm, more preferably less than 500 μm, more preferably less than 100 μm, and further preferably less than 50 μm. On the other hand, the lower limit of the particle size of the graphene aggregate is not particularly limited, for example, it can also be about 1 μm. The particle size of the graphene aggregate can be measured by observation using an electron microscope.

[0059] <Carbon structure>

[0060] Hereinafter, the three-dimensional carbon structure including the nanocarbon structure having a petal-like structure and / or a concavo-convex structure of the present invention will be described.

[0061] The three-dimensional carbon structure includes a nanocarbon structure having at least one of a petal-like structure and a concavo-convex structure. Here, the nanocarbon structure preferably has a petal-like structure, and more preferably has a petal-like structure and a concavo-convex structure.

[0062] (petal-like structure)

[0063] The petal-like structure in the present invention refers to a structure formed by fixing a thin sheet of carbon having a graphene skeleton with a thickness of less than 20 nm into a petal-like shape ( Figures 4 to 6 Here, the lower limit of the thickness of the flaky carbon is not particularly limited, and may be greater than the thickness of a single-layer graphene (approximately 0.34 nm).

[0064] (Concave-convex structure)

[0065] The concavoconvex structure in the present invention refers to a fine structure including concavoconvexity formed by the aggregation of seed-like structures of 1 to 100 nm in size ( Figure 7 to Figure 12 Etc.). Here, the size of the concavo-convex in the concavo-convex structure is preferably greater than 1 nm. The size of the concavo-convex may also be greater than 5 nm, or greater than 10 nm. On the other hand, the size of the concavo-convex is preferably less than 90 nm, more preferably less than 80 nm, further preferably less than 70 nm, further preferably less than 60 nm, further preferably less than 50 nm, further preferably less than 40 nm, further preferably less than 30 nm. The range of the size of the concavo-convex is, for example, preferably in the range of 1 to 90 nm, more preferably 1 to 80 nm, further preferably 1 to 70 nm, further preferably 1 to 60 nm, further preferably 1 to 50 nm, further preferably 1 to 40 nm, further preferably 1 to 30 nm.

[0066] For example, in Fig.11 In the SEM (observed at a magnification of 300,000 times), the scale is shown as 100 nm, and it can be confirmed that the granular and nodular concave-convex structures below 100 nm are connected into beads, chains and grapes, and exist in straight lines, spirals and radials. Fig.12 Yes Fig.11 The part surrounded by the rectangle is magnified 800,000 times. Fig.12 The scale bar in the figure is 50 nm, and it can be confirmed that the structure also has a concavo-convex structure in the range of 1 to 50 nm.

[0067] (Three-dimensional carbon structure)

[0068] In the three-dimensional carbon structure of the present invention, the three-dimensional shape is not particularly limited, and includes any shape of a structure or a part of the structure that can be used for reflection of cold neutrons or ultracold neutrons. Fig.26As shown in the figure, the three-dimensional shape can be specifically exemplified by: a plate-like shape as (a), a disc-like shape as (b), a tube-like shape as (c), a square tube-like shape as (d), etc. Furthermore, it can be a shape of a split piece formed by splitting a tube-like shape as (e), or a shape of a split piece formed by splitting a square tube-like shape as (f). Alternatively, it can be a shape of a connected body formed by connecting tubes as (g), or a shape of a connected body formed by connecting square tubes as (h).

[0069] (Bending Strength)

[0070] The three-dimensional carbon structure of the present invention needs to be arranged in the form of a component in a neutron generating device as a neutron reflector, so it is necessary not to break or damage during the processing when making the device and when fixing it with screws, etc. In addition, as a neutron reflector, when used continuously in the device, it is necessary to be able to be used continuously without being damaged or broken due to vibration, etc. Therefore, the three-dimensional carbon structure as a neutron reflector needs to be in a state that does not contain a binder other than carbon, and has good formability and mechanical strength. From this point of view, the bending strength of the three-dimensional carbon structure of the present invention is preferably 0.5MPa or more. This is because it is necessary to have a certain degree of bending strength when used as a reflector for cold neutrons or ultracold neutrons. The bending strength is preferably 0.7MPa or more, more preferably 0.9MPa or more, further preferably 1.0MPa or more, and further preferably 2.5MPa or more. On the other hand, the upper limit of the bending strength is not particularly limited, and is usually about 10.0MPa. It should be noted that the bending strength can be measured by the method described in the embodiment.

[0071] (Volume Density)

[0072] The three-dimensional carbon structure of the present invention is characterized by having a desired nano-sized fine structure for effectively scattering and reflecting neutrons, and it is believed that the more the fine structure exists, the better. Therefore, it is preferred to have as many desired fine structures as possible and have the desired mechanical strength. From the viewpoint of not containing a binder other than carbon, having good formability and desired mechanical strength, and excellent neutron reflection ability, the volume density is preferably 0.70 g / cm 3 More preferably 0.80 g / cm 3 More preferably, 0.90 g / cm 3 On the other hand, the upper limit of the bulk density is not particularly limited, but is usually 2.2 g / cm 3 However, from the perspective of neutron reflection ability, it can be 1.10 g / cm 3 Below, can also be 1.00g / cm 3Below, can also be 0.95g / cm 3 Below, it can also be 0.91g / cm 3 The bulk density can be measured by the method described in the examples.

[0073] (Raman spectroscopy)

[0074] The three-dimensional carbon structure of the present invention preferably has a peak intensity ratio of the G band to the D band G / D obtained by Raman spectroscopy of 3.00 or more, and a peak intensity ratio of the G band to the 2D band G / 2D of 3.00 or less.

[0075] About G / D, G band tends to the more regular the stacking structure of graphene is, the higher the peak value is, and D band tends to increase with the disorder and defects of the stacking structure of graphene, the higher the peak value is, thus indicating that the higher the G / D is, the more regular graphite structure can be formed. G / D is preferably more than 3.30, more preferably more than 4.30, more preferably more than 5.30, more preferably more than 6.30, more preferably more than 6.90. On the other hand, the upper limit of G / D is not particularly limited, usually about 12.00.

[0076] About G / 2D, the more regular the stacking structure of graphene is, the higher the peak value is, but the 2D band tends to decrease as the number of stacking of graphene is higher, thus indicating that the lower the G / 2D is, the thinner the stacking structure of graphene (i.e., the structure closer to graphene) can be formed. G / 2D is preferably less than 3.00, more preferably less than 2.50, more preferably less than 2.00, more preferably less than 1.93, more preferably less than 1.50, and more preferably less than 1.00. On the other hand, the lower limit of G / 2D is not particularly limited, and is generally about 0.50.

[0077] In addition, the Raman spectrum can be measured by the method described in the Examples (microscopic laser Raman spectroscopy).

[0078] (thickness)

[0079] The three-dimensional carbon structure of the present invention can use carbon structures of various thicknesses according to the purpose, so the thickness is not particularly limited. Moreover, the three-dimensional carbon structure of the present invention has high formability, so it can be made into a structure of various thicknesses from thin to thick. For example, the three-dimensional carbon structure can be more than 0.1 mm, or more than 1.0 mm, or more than 10 mm, or more than 100 mm. This is because it is suitable for use as a reflector for cold neutrons or ultracold neutrons. On the other hand, the upper limit of the thickness is not particularly limited, and can generally be about 100 mm, or about 400 mm or about 800 mm.

[0080] (Neutron transmittance)

[0081] The neutron transmittance of the three-dimensional carbon structure of the present invention to 0.5 meV neutrons is preferably 80% or less. This is because it is suitable for use as a reflector for cold neutrons or ultracold neutrons. The neutron transmittance is preferably 70% or less, more preferably 60% or less, further preferably 55% or less, and further preferably 53% or less. On the other hand, there is no particular restriction on the lower limit of the neutron transmittance, the lower the better, but in the case of nanodiamonds, it is about 44%. The neutron transmittance can be measured using the method described in the embodiments.

[0082] <Manufacturing method>

[0083] The three-dimensional carbon structure of the present invention can be produced by at least the following method: That is, it can be produced by mixing a nanocarbon structure as a raw material and a carbon binder and then molding the mixture.

[0084] (Nanocarbon Structure)

[0085] The nanocarbon structure is a carbon material having at least one of a petal-like structure and a concavo-convex structure, wherein the petal-like structure is formed by fixing a thin sheet of carbon having a graphene skeleton with a thickness of less than 20 nm into a petal-like shape, and the concavo-convex structure is formed by aggregating seed-like structures of 1 to 100 nm in size. The meanings of the petal-like structure and the concavo-convex structure are as shown above. In addition, the nanocarbon structure preferably has both the petal-like structure and the concavo-convex structure.

[0086] (Carbon Binder)

[0087] Carbon binder refers to a carbon material used as a binder in order to form a nano carbon structure. As a specific example of a carbon binder suitable for obtaining a three-dimensional carbon structure of the present invention, thermal expansion graphite and graphene aggregates can be cited. Among them, preferred graphene aggregates. The meanings of thermal expansion graphite and graphene aggregates are as shown above. However, in the present invention, the carbon binder is not limited as long as it can form a nano carbon structure and can also be used as a reflective material for cold neutrons or ultracold neutrons to fully maintain and function after forming the nano carbon structure. If it is such a carbon material, the carbon material other than thermal expansion graphite and graphene aggregates can also be used as a carbon binder.

[0088] (mix)

[0089] The mixing method of nano carbon structure and carbon binder is not particularly limited, and can be implemented according to a conventional method. This mixing can be implemented by using a ball mill etc. to mix the nano carbon structure with the carbon binder. In addition, when the carbon binder is a graphene aggregate, it is also possible to be in the state of graphene being dispersed in an alcohol isosolvent in its manufacturing process, by adding the nano carbon structure thereto and mixing, then separating the solvent to manufacture.

[0090] (Mixture ratio)

[0091] Regarding the mixing ratio of the nano-carbon structure and the carbon binder when mixing the nano-carbon structure and the carbon binder, from the viewpoint of ensuring formability, the mass ratio of the nano-carbon structure and the carbon binder is preferably 5.0 or less, more preferably 4.5 or less, further preferably 4.0 or less, and further preferably 3.5 or less. On the other hand, from the viewpoint of high strength of cold neutrons or ultracold neutrons, the mixing ratio is preferably 1.0 or more, more preferably 1.5 or more, further preferably 2.0 or more, and further preferably 2.5 or more.

[0092] (Forming)

[0093] The molding of the mixture thus obtained can be implemented in the following manner: using a mold corresponding to the shape of the three-dimensional carbon structure as the target object, filling the mixture therein, applying a desired load. By such operation, carbon binder is utilized to bond the nano carbon structure to form a three-dimensional carbon structure. In this case, the mold preferably has a vacuum suction mechanism, and can further have a heating mechanism, so that heating is performed for hot pressing during load forming. As a molding method, various molding methods such as compression molding, inflation molding, Engel molding, extrusion molding, extrusion lamination molding, rotation molding, calendering molding, injection molding, vacuum molding, stamping molding, injection molding, coagulation molding, lamination molding, casting molding, injection molding, manual layered molding, low pressure molding, transfer molding, foaming molding, hand paste molding (hand lay-up) method, filament winding method, blow molding, powder molding, mold forming, SMC method (sheet molding compound, Sheet Molding Compound), T mold method can be applied.

[0094] When the mold has a vacuum suction mechanism, it is preferred to adjust the vacuum degree in the mold to 100 Pa or less before load forming. In addition, when the mold has a heating mechanism, it is preferred to set the temperature of the mold to 50°C or more before load forming. The load during load forming is preferably 2 to 100 kN / cm 2 , more preferably 5 to 70 kN / cm 2 , more preferably 7 to 50 kN / cm 2 , more preferably 10 to 30 kN / cm2 The load forming time is preferably 0.5 to 20 minutes, more preferably 1 to 10 minutes, and even more preferably 1 to 5 minutes.

[0095] (Cutting)

[0096] The three-dimensional carbon structure formed into a certain shape can be used directly, or it can be further cut (sliced) as needed to make a carbon structure of desired thickness. The thickness of this carbon structure is not particularly limited, for example, it can be more than 0.1 mm, it can be more than 1.0 mm, it can be more than 10 mm, and it can be more than 100 mm. On the other hand, the thickness can also be about 400 mm. The range of this thickness can be, for example, 1 to 100 mm, 1 to 50 mm. Moreover, this cutting process can be appropriately implemented using a multi-wire saw or the like.

[0097] (Raw material production method)

[0098] The nanocarbon structure as a raw material of the three-dimensional carbon structure of the present invention and the graphene aggregate as a carbon binder can be produced as follows.

[0099] Nanocarbon structures

[0100] The nanocarbon material of the present invention can be produced, for example, by calcining an organic compound such as a phenolic resin once, placing the calcined raw material in a sealed container made of a heat-resistant material, and performing hot isostatic pressing (HIP) treatment in the presence of an inert gas (such as argon).

[0101] Organic compounds

[0102] As the organic compound, any organic compound that can be carbonized by heating and firing can be used, for example, the following organic compounds can be used: natural organic polymers, such as starch, cellulose, protein, collagen, alginic acid, dammar, copal, rosin, gutta percha, natural rubber, etc.; semi-synthetic polymers, such as cellulose resins, cellulose acetate, cellulose nitrate, cellulose acetate butyrate, casein plastics, soy protein plastics, etc.; synthetic polymers, such as phenolic resins and urea resins as thermosetting resins; resin), melamine resin, benzoguanamine resin, epoxy resin, diallyl phthalate resin, unsaturated polyester resin, bisphenol A type epoxy resin, novolac type epoxy resin, multifunctional epoxy resin, alicyclic epoxy resin, alkyd resin, polyurethane resin, and polyester resin as thermoplastic resin (polyethylene terephthalate (PET) resin, polytrimethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, polynaphthalate resin) butylene glycol dicarboxylate resin, etc.), vinyl chloride resin, polyethylene, polypropylene, polystyrene, etc.; synthetic rubber, such as polyisoprene rubber, butadiene rubber, etc.; synthetic fiber, such as nylon, vinylon, acrylic fiber, rayon, etc.; and others such as polyvinyl acetate, ABS resin, AS resin, acrylic resin, polyacetal, polyimide, polycarbonate, modified polyphenylene ether (PPE), polyarylate, polysulfone, polyphenylene sulfide, polyetheretherketone, fluororesin, polyamideimide, silicone resin, etc. These organic compounds can be used alone or in combination of two or more.

[0103] It should be noted that petroleum-based asphalt, coal-based asphalt, petroleum coke, coal coke, carbon black, and activated carbon generated in the refining process of fossil fuels such as petroleum and coal can of course be used. From the perspective of forming a resource-recycling society and effectively utilizing carbon in waste, the introduction of carbonization systems is being promoted in various places. Waste plastics, waste PET bottles, waste wood, waste plants, food waste such as kitchen waste, etc., which are mixtures of the above-mentioned various resins, can also be used as raw material organic compounds in the same way as above.

[0104] Burn-in

[0105] Pre-calcination is a step of pre-heating and burning the organic compound as a raw material to make it suitable for HIP treatment. Pre-calcination can be carried out using an intermittent furnace, a muffle furnace, a high-continuous multi-tube furnace, or an internally heated rotary kiln or a swing kiln. The pre-calcination atmosphere is preferably carried out in an inert atmosphere such as a nitrogen gas flow at a predetermined heating rate and pre-calcination temperature.

[0106] Generally, organic compounds are polymerized by heating, and oxygen, nitrogen, and hydrogen atoms in the structure become thermodynamically unstable and are released, thereby carbonizing. Therefore, most organic compounds undergo these reactions by heat treatment at about 300° C. or above, and become pre-burned raw materials with residual carbon and appropriate amounts of hydrogen, oxygen, nitrogen, etc. at about 400° C. or above, so in the present invention, the organic compound pre-burned in this way can be used as the pre-burned raw material.

[0107] In the present invention, the pre-firing temperature (maximum temperature during pre-firing) is usually preferably 500°C to 1000°C, more preferably 550°C to 850°C, and further preferably 600°C to 700°C. The pre-firing time depends on the type and amount of the raw materials, the pre-firing temperature, etc., but is usually preferably performed for about 1 to 6 hours. The appropriate pre-firing temperature and time can be determined based on the amount of residual hydrogen in the pre-firing raw materials. From the viewpoint of fully generating gases such as hydrogen, hydrocarbons, carbon monoxide, and water vapor required for the CVD reaction during the HIP treatment, the appropriate amount of residual hydrogen in the pre-firing raw materials is usually about 6500 ppm or more, preferably about 10000 ppm or more, and further preferably about 20000 ppm or more.

[0108] Sealed container made of heat-resistant material

[0109] During the HIP treatment, the pre-burned raw material is placed in a closed container made of a heat-resistant material. The container is used as a reaction container for causing CVD reactions in gases such as hydrogen, hydrocarbons, carbon monoxide, and water vapor generated by the pre-burned raw material during the HIP treatment. While maintaining the isotropic high pressure caused by the gas pressure, a chemical reaction occurs without diffusing the reaction gas generated inside to the outside. As heat-resistant materials constituting the container, in addition to graphite, ceramics such as aluminum oxide, magnesium oxide, and zirconium oxide, as well as metals such as iron, nickel, zirconium, and platinum can also be cited. The material of the container (such as a crucible) is preferably a graphite material. When a graphite crucible is used as the container, the open porosity (apparent porosity) of the graphite material is preferably less than about 20%. This is because the concentration of the reaction gas in the container can be maintained at a desired level during the HIP treatment. In addition, from the perspective of effectively removing the product after the HIP treatment, the graphite crucible is preferably a threaded graphite crucible. In addition, examples of the types of threads in the threaded graphite crucible include triangular threads (a cross section of a thread ridge of the thread is a shape close to an equilateral triangle), square threads, trapezoidal threads, etc. Among them, triangular threads are preferred.

[0110] Hot Isostatic Pressing (HIP)

[0111] The HIP treatment can be carried out in the following manner: after placing the pre-calcined raw material in a closed container made of a heat-resistant material, the pre-calcined raw material together with the container is placed in a HIP treatment device, and the HIP treatment is carried out in the presence of an inert gas.

[0112] As the inert gas, an inert gas generally used in this field, such as argon gas and nitrogen gas, can be used.

[0113] The temperature during HIP treatment is preferably such that the maximum temperature is higher than the calcination temperature and is about 900°C or more, more preferably about 1000°C or more, further preferably 1100°C or more, and further preferably 1200°C or more. On the other hand, in order to prevent the target from being damaged by etching caused by excited hydrogen, the maximum temperature is about 2000°C, preferably 1900°C or less, further preferably 1800°C or less, and further preferably 1600°C or less. It should be noted that the maximum temperature during HIP treatment is preferably a temperature that is usually 100°C or more higher than the calcination temperature, and more preferably 400°C or more higher. The maximum pressure during HIP treatment varies depending on the particle size of the calcined raw material, and is generally preferably about 1 MPa to about 300 MPa, more preferably about 10 MPa to about 200 MPa, and further preferably about 30 MPa to about 200 MPa. For example, when the particle size of the calcined raw material is large, a larger maximum pressure is preferred, while when the particle size is small, a smaller pressure is often sufficient. In the HIP process, from the perspective of production efficiency, it is usually desired to increase the pressure to a predetermined pressure (pressure first mode) before increasing the temperature to near the calcining temperature, and then increase the temperature to near the calcining temperature without scattering the calcined raw material, and then increase the temperature and pressurize as needed to reach the maximum temperature and the maximum pressure. On the other hand, in the case of a small particle size such as about 1 μm or less, the pressure first mode as described above is not particularly required, and the HIP process can be effectively implemented.

[0114] In the HIP process, the pre-burned raw material is isotropically pressurized using an inert gas as a pressure medium. Therefore, in the initial stage of the HIP process, a high-pressure, high-density phase is formed around the pre-burned raw material particles by the inert gas. Afterwards, when the HIP process temperature becomes higher than the pre-burning temperature, gas begins to be generated from the pre-burned raw material, but since the diffusion coefficient of the gas to the high-pressure, high-density pressure medium becomes smaller, a high-concentration reaction gas area (hydrogen, hydrocarbons, carbon monoxide, etc.) is formed around the pre-burned raw material. Since the HIP process is isotropically pressurized, the reaction gas area is uniformly formed on the outer surface of the particle and is similar to the shape of the particle.

[0115] In these reaction gas regions, when the HIP treatment temperature becomes higher, specifically up to about 900°C or more, a so-called thermal CVD (Chemical Vapor Deposition) reaction occurs, and gas-phase grown graphene is precipitated. The CVD reaction, which is usually carried out by supplying reaction gas to the substrate surface using a CVD device, a plasma CVD device, etc., can be carried out in the reaction gas region generated around the pre-burned raw material in a container made of heat-resistant material using a HIP device.

[0116] In addition, about the particle size of the pre-fired raw material used, since the CVD reaction mainly occurs on the surface of the particles, if the particle size is large, the ratio of the surface area to the volume becomes smaller, and as a result, the amount of gas-grown graphene in the obtained material is reduced. Therefore, it is preferred to use a raw material with a small particle size because the generation rate of gas-grown graphene can be improved. From the viewpoint of production efficiency, when using a spherical resin, it is preferred to use a spherical resin with a particle size (average) of about 100 μm or less. In the case of using a material that will temporarily melt during the pre-fired process (such as a thermoplastic resin, etc.) as a raw material, as long as the pre-fired raw material is crushed and classified in advance when the HIP treatment is performed, the pre-fired raw material of the desired size can be obtained. For example, a foam (brittle sponge-like material) is obtained after the thermoplastic resin is pre-fired, so when the foam is subjected to the HIP treatment, it is pre-crushed and then classified to make a pre-fired raw material of the desired size.

[0117] Through the above HIP treatment, a nano-carbon structure having a petal-like structure and / or a concave-convex structure can be obtained.

[0118] Carbon Binder

[0119] Among carbon binders, heat-expandable graphite can be produced by, for example, rapidly heating a graphite intercalation compound and causing graphite particles formed by overlapping carbon hexagonal network surfaces to expand several hundred times in the thickness direction.

[0120] In addition, a graphene aggregate can be prepared, for example, by dispersing a single layer or multiple layers of graphene in a solvent containing a lower alcohol (e.g., isopropyl alcohol) or water to prepare a graphene dispersion, dropping the graphene dispersion onto filter paper, allowing the dispersion to precipitate while separating the solvent, drying the thus obtained precipitate to remove the solvent, and then pulverizing the precipitate as needed to prepare a graphene aggregate.

[0121] Here, the graphene dispersion can be prepared by various methods. For example, it can be prepared in the following manner: the heat-expanded graphite obtained by heat-treating the graphite intercalation compound is immersed in isopropanol, crushed with a homogenizer, and then centrifuged to separate the supernatant to prepare the graphene dispersion. Alternatively, it is also possible to replace the heat-expanded graphite in the above method and use "the raw materials such as phenolic resin powder pre-sintered to contain residual hydrogen are filled into a graphite container, and the bulk graphene block obtained by hot isostatic pressing together with the container under an inert gas atmosphere" (International Publication No. 2011 / 102473), which is immersed in isopropanol and then the subsequent process is carried out. Alternatively, the heat-expanded graphite can also be replaced by "natural graphite particles (for example, high-purity natural graphite powder, earthy graphite powder, etc. that can be purchased from SEC Carbon Co., Ltd. (SEC CARBON, LIMITED) and Nippon Graphite Industries, Co., Ltd.)".

[0122] In addition, as the graphene dispersion, for example, a graphene dispersion “GF10IPA-D0N” manufactured by INCUBATION ALLIANCE, INC., etc. may be used.

[0123] The multilayer graphene constituting the graphene aggregate is not particularly limited as long as it can be used as the carbon binder of the present invention, and multilayer graphene produced by a production method other than the above-mentioned production method may also be used.

[0124] <Other manufacturing methods>

[0125] The three-dimensional carbon structure of the present invention may be produced by other production methods other than the above production method as long as it includes a predetermined petaloid structure and / or a predetermined concavo-convex structure. In addition, these other production methods do not necessarily require the use of a carbon binder.

[0126] <Application>

[0127] The three-dimensional carbon structure of the present invention obtained in this way can be used as a reflector for cold neutrons or ultracold neutrons, and can be effectively used in a wide range of fields such as structural analysis of materials, life sciences, and medicine.

[0128] Example

[0129] Hereinafter, the present invention will be described based on examples, but the present invention is not limited to the examples.

[0130] <Materials used in production examples>

[0131] Resin: Bellpearl R800 (spherical phenolic resin manufactured by Air Water Bellpearl Co., Ltd., average particle size 15 μm)

[0132] Expandable graphite: SS-3 (manufactured by Air Water Performance Chemical Co., Ltd.)

[0133] <Manufacturing example>

[0134] Production Example 1 (Nanocarbon Structure)

[0135] The nanocarbon structure was prepared according to the description in Table 1. That is, the resin as a raw material was put into an artificial graphite crucible (extrusion type PSG-12 manufactured by TOHO CARBON CO., LTD.), and the crucible was placed in a stainless steel muffle furnace equipped with pipes for introducing and discharging the atmosphere gas, and the muffle furnace was set in a small box furnace (KBF828N1) manufactured by Koyo Thermal Systems. The structure of the stainless steel muffle furnace is as follows Figure 1 As shown. The muffle furnace is composed of a muffle furnace body 1, heat-resistant rubber (for sealing) 2, and a muffle furnace cover 3. Each part has a fixing screw hole 4. The muffle furnace cover 3 has an atmosphere gas inlet 5 and an atmosphere gas outlet 6. By circulating 2 to 3 L / min of atmosphere gas, the resin and carbide can be prevented from being oxidized during pre-burning. At the same time, the water vapor, carbon dioxide, carbon monoxide, nitrogen oxides, tar-like low-boiling hydrocarbons, etc. generated during pre-burning are discharged, thereby stably pre-burning. A water-cooling pipe is embedded in the interior of the muffle furnace cover 3, and the water cooled by the cooler is circulated through the cooling water inlet 7 and the cooling water outlet 8 to prevent the muffle furnace cover 3 and the small box furnace from overheating. The temperature of the small box furnace is set to a heating rate of 300°C / h in the temperature range of room temperature to 150°C (this process mainly removes moisture absorbed and adsorbed in the resin), the heating rate in the temperature range of 150-400°C is set to 15°C / h (this process mainly gasifies elements such as hydrogen, oxygen, nitrogen, and sulfur in the chemical structure of the resin), and the heating rate in the temperature range of 400°C to the pre-burning temperature is set to 20°C / h (this process mainly starts carbonization), and the temperature is increased. After reaching the predetermined pre-burning temperature, pre-burning is carried out at the pre-burning temperature for 5 hours.

[0136] The pre-sintered resin (powder) is placed in an artificial graphite crucible (made of CIP material MGY-71 manufactured by Toho Carbon Co., Ltd.) that can be sealed by a threaded upper cover, and then placed in a pressure vessel of a hot isostatic pressing device (O2-Dr.HIP manufactured by Kobe Steel Co., Ltd.) for heating and pressurization treatment (HIP treatment). Using argon as the gas medium, the temperature is increased at a rate of 600°C / h while evacuating the temperature range from room temperature to 200 degrees, the temperature is increased at a rate of 450°C / h in the temperature range from 200 to 500°C, the temperature is increased at a rate of 850°C / h in the temperature range from 500 to 900°C, and the temperature is increased at a rate of 750°C / h in the temperature range from 900 to the maximum reached temperature, and the pressure is increased at the same time. After reaching the predetermined maximum reached temperature and maximum reached pressure, the temperature and pressure are maintained for a predetermined time to perform HIP treatment. The results are recorded in Table 1.

[0137] [Table 1] Table 1

[0138]

[0139] The SEM image of the nanocarbon structure 1 is as follows: Figure 2 and Figure 3 As shown. Figure 2 On the other hand, the formation of a concavoconvex structure was not confirmed. Figure 3 Yes Figure 2 This is an enlarged view of the portion where the generation of flaky carbon was confirmed.

[0140] On the other hand, the SEM image of the nanocarbon structure 2 is as follows: Figures 4 to 12 shown. Figure 4 The spherical shape of the raw material resin is reflected in FIG. 1 , and it can be confirmed that a petal-shaped structure in which flaky carbon is fixed in a petal shape is significantly generated from the surface of the sphere. Figure 5 and Figure 6 The petal-shaped structure is magnified 50,000 times and 100,000 times respectively. Referring to the 100nm scale bar in the photo, it can be seen that the single flake of carbon that constitutes the petal-shaped structure is less than 20nm thick. Figure 7 and Figure 8 It was confirmed that a concavo-convex structure was formed by agglomeration of seed-like structures inside the carbon spheres having a petal-like structure on the surface. Figures 9 to 12 The enlarged photographs of the generated concavo-convex structure are shown. Referring to the scale bar of 100 nm in these figures, it can be confirmed that the concavo-convex structure is a fine structure formed by aggregation of seed-like structures of 1 to 100 nm in size. Fig.12 yes Fig.11 An enlarged view of the part surrounded by the box.

[0141] Production Example 2 (Carbon Binder)

[0142] Production Example 2-1 (Thermal expansion graphite)

[0143] 5 g of thermal expansion graphite (SS-3) was placed in an artificial graphite crucible (Extrusion type PSG-12 manufactured by Toho Carbon Co., Ltd.), and the crucible was placed in an electric furnace set at 750°C for 10 minutes to obtain 4.5 g of thermal expansion graphite that expanded several hundred times in the thickness direction of the graphite particles. The obtained thermal expansion graphite was collected in a 100 cm 3 Use a glass rod with an outer diameter of 10 mm to scrape the top of the aluminum measuring cup to remove excess thermal expansion graphite to make it 100 cm 3 Next, the volume value of thermally expanded graphite was measured using an analytical electronic balance HTR-80 (manufactured by Shinko Electronics Co., Ltd., analysis accuracy 0.1 mg) at 100 cm 3 The weight of the thermally expanded graphite is divided by the volume (100 cm 3 ), and the tap density was calculated to be 0.018 g / cm 3 .

[0144] Production Example 2-2 (Graphene Aggregate)

[0145] The 4g of heat-expanded graphite obtained above was immersed in 500ml of isopropanol in a glass beaker, and then a universal homogenizer (Physcotron NS52 manufactured by MICROTEC CO., LTD.) was used to perform a crushing process for 15 minutes × 8 times at a rotation speed of 12500rpm. The ultrasonic oscillator of an ultrasonic homogenizer (US300T manufactured by Nippon Seiki Co., Ltd.) was put into the crushed product, and an ultrasonic treatment was performed for 10 minutes × 20 times with an output of 70%, and the heat-expanded graphite particles were crushed to free graphene (including multilayer structures in addition to single-layer structures). The obtained mixed solution was placed for 12 hours, and the supernatant was recovered to obtain a graphene dispersion. 50g of the obtained graphene dispersion was collected in an aluminum cup with an acid-resistant aluminum treatment on the surface, and after being kept at 90°C for 20 hours, the mass of the solid content was measured, and the solid content was calculated from the mass ratio of the dispersion, and the result was 0.8% by mass.

[0146] A filter paper (quantitative filter paper 5A manufactured by Advantec Toyo Co., Ltd.) is loaded on a Buchnaroto funnel, and the above-obtained graphene dispersion is slowly dripped while decompressing with a suction device, and graphene and isopropanol are separated, so that graphene is deposited on the filter paper. After the sediment is air-dried at room temperature for 5 hours, it is dried for 8 hours in an electric furnace set at 90°C, and isopropanol is completely removed to obtain a solid substance (graphene sediment). The solid substance is crushed into coarse particles using a universal grinder (M20, manufactured by ASONE Co., Ltd.) with a crushing time of 15 minutes, and is classified with a stainless steel sieve with an aperture of 100 μm to obtain a graphene aggregate less than 100 μm.

[0147] Fig.13 SEM image of thermally expanded graphite is shown. Fig.14 A SEM image of a graphene aggregate is shown.

[0148] <Materials used in Examples>

[0149] Nanocarbon structure 1: Nanocarbon structure produced in Production Example 1

[0150] Nanocarbon structure 2: Nanocarbon structure produced in Production Example 1

[0151] Carbon binder 1: thermally expanded graphite prepared in Preparation Example 2-1 (tap density: 0.018 g / cm 3 )

[0152] Carbon binder 2: Graphene aggregate produced in Production Example 2-2

[0153] <Example>

[0154] (Three-dimensional carbon structure)

[0155] Using the nanocarbon structure and the carbon binder, a three-dimensional carbon structure was prepared according to the description in Table 2. For example, the three-dimensional carbon structure 7 was obtained by placing the nanocarbon structure 2 and the carbon binder 2 in a plastic container, shaking them thoroughly to mix them thoroughly, and then using a metal mold (disc-shaped with an outer diameter of 25 mm) to perform pressure molding under a load of 30 kN.

[0156] Similarly, only the nanocarbon structure 1, only the nanocarbon structure 2, only the carbon binder 2, the mixture of the nanocarbon structure 1 and the carbon binder 1, the mixture of the nanocarbon structure 1 and the carbon binder 2, and the mixture of the nanocarbon structure 2 and the carbon binder 1 were press-formed (under conditions such as 20 to 30 kN) (they are three-dimensional shaped carbon structures 1 to 6, respectively).

[0157] The three-dimensional carbon structure 1 formed by molding only the nanocarbon structure 1 and the three-dimensional carbon structure 2 formed by molding only the nanocarbon structure 2 were very brittle and could not be molded smoothly. The three-dimensional carbon structure 3 formed by molding only the carbon binder 2 had good moldability.

[0158] The three-dimensional carbon structure 4 obtained by molding a mixture of the nanocarbon structure 1 and the carbon binder 1 (thermal expansion graphite) with a large molding force has multiple fine cracks and becomes a slightly uneven molded body. The three-dimensional carbon structure 5 obtained by molding a mixture of the nanocarbon structure 1 and the carbon binder 2 (graphene aggregate) may have cracks in the molded body due to the slightly insufficient growth of the flaky carbon on the surface of the nanocarbon structure 1. Fine cracks were also confirmed in the three-dimensional carbon structure 6 obtained by molding a mixture of the nanocarbon structure 2 and the carbon binder 1 (thermal expansion graphite). It can be seen that the three-dimensional carbon structures 4 to 6 were all confirmed to have some unevenness or cracks in the molded body, but they were able to be fully molded.

[0159] The three-dimensional carbon structure 7 obtained by molding the mixture of the nanocarbon structure 2 and the carbon binder 2 exhibits good moldability.

[0160] Figure 15 to Figure 19 The results of visual observation of the three-dimensional carbon structures 3 to 6 are shown (photographs).

[0161] in addition, Figure 20 to Figure 25 The results (SEM images) of observing the three-dimensional carbon structures 4, 6 and 7 using a scanning electron microscope (SEM) are shown.

[0162] Fig. 20 This is a SEM image of the three-dimensional carbon structure 4. It can be confirmed that the petal-like structure derived from the nanocarbon structure 1 is covered with the carbon binder. However, it can be inferred that the petal-like structure exists inside.

[0163] Fig.21 : is a SEM image of the three-dimensional carbon structure 6. It is possible to confirm the region where the petaloid structure and the concavo-convex structure derived from the nanocarbon structure 2 are covered by the carbon binder, but it is also possible to confirm the region where they are not covered.

[0164] Fig. 22 : is a SEM image of a three-dimensional carbon structure 7. It can be confirmed that the petal-shaped structure and the concavo-convex structure derived from the nanocarbon structure 2 are not covered by the carbon binder. Fig.21 There are more cases. Figure 23 to Figure 25 This is a further enlarged SEM image. Fig.23 Petal-like structures and concave-convex structures can be confirmed. Fig.24 and Fig.25 This is a further enlarged SEM image of the concavoconvex structure.

[0165] [Table 2] Table 2

[0166]

[0167] The predetermined three-dimensional carbon structure in the three-dimensional carbon structure obtained above was analyzed by microscopic laser Raman spectroscopy, and the bending strength was measured. The results are shown in Table 3. Regarding the microscopic laser Raman spectroscopy, as a reference, high crystalline graphite (GRAPHTEC SS400 (thickness 240 μm), Reference Example 2) and artificial graphite plate (CIP material MGY-71 manufactured by Toho Carbon Co., Ltd., Reference Example 3) were also evaluated.

[0168] (Micro-Raman spectroscopy)

[0169] Each carbon structure was analyzed using a Raman spectroscopic analyzer (XploRA manufactured by Horiba, Ltd., excitation wavelength 531.12 nm, Ar laser) to obtain a spectrum based on Raman spectroscopy. From the spectrum, the G / D ratio, i.e., the ratio of the peak intensity of the G band to the peak intensity of the D band, which is an indicator of the crystallinity of the sp2 carbon bond (graphene structure), and the G / 2D ratio, i.e., the ratio of the peak intensity of the G band to the peak intensity of the 2D band, which is an indicator of the small number of graphene stacking layers, were calculated.

[0170] (Bending Strength)

[0171] For each carbon structure, a disc-shaped sample with an outer diameter of 25 mm (thickness of about 2 to 4 mm) was prepared. For each sample, a load tester (ZTA-2500N) and a bending test unit (MX2) of IMADA Co., Ltd. were used to measure the load displacement curve under the conditions of a fulcrum distance of 20 mm and a pressing speed of 10 mm / min, and the maximum load when the material was bent was measured. The maximum stress was calculated by dividing the obtained maximum load by the cross-sectional area of ​​the sample, and this value was used as the bending strength. The sample of Example 1 buckled under a load of 6N (bending strength 1.0MPa), and the sample of Example 3 buckled under a load of 12N (bending strength 1.6MPa).

[0172] [Table 3] Table 3

[0173]

[0174] Compared with artificial graphite (Reference Example 3) which is a general graphite material, the three-dimensional carbon structure of the embodiment has a higher G / D ratio and a lower G / 2D ratio, indicating that the embodiment is composed of graphene with high crystallinity and a small number of stacking layers of sp2 carbon bonds (graphene structure).

[0175] The three-dimensional carbon structure 3 (reference example 1) formed by only the carbon binder 2 has a high G / D value, but since it does not contain a petal-shaped structure and a concavo-convex structure, G / 2D is a large value of 3.38. The high crystalline graphite also has a high G / D value, but G / 2D is a large value of 3.26.

[0176] The three-dimensional carbon structure 4 (Example 1) formed by the mixture of the nano-carbon structure 1 and the carbon binder 1 (thermal expansion graphite) with a large forming force has a G / D higher than that of artificial graphite and a G / 2D lower than that of artificial graphite. The three-dimensional carbon structure 6 formed by the mixture of the nano-carbon structure 2 and the carbon binder 1 (thermal expansion graphite) also has a G / D higher than that of artificial graphite and a G / 2D lower than that of artificial graphite (Example 2).

[0177] Furthermore, in the three-dimensional carbon structure 7 obtained by molding the mixture of the nano-carbon structure 2 and the carbon binder 2, the petal-shaped structure in which the flaky carbon is fixed to the petal shape and the concavo-convex structure formed by the aggregation of the seed-shaped structure of 1 to 100 nm in size are fully grown on the particle surface of the nano-carbon structure 2, and even after being matched with the graphene aggregate, a molded body (Example 3) in which a large number of petal structures and concavo-convex structures can be confirmed in the SEM image is obtained. Its G / D is higher than that of other embodiments, and G / 2D is lower than that of other embodiments. In addition, the bending strength also shows a large value (1.6MPa).

[0178] SEM images of the three-dimensional carbon structures of Examples 1 to 3 ( Figure 20 to Figure 25 ),exist Fig. 20 In (three-dimensional nanocarbon structure 4), the surface is completely covered by the carbon binder, and the petal-like structure cannot be confirmed, but it can be inferred that the petal-like structure is maintained under the carbon binder. This is because: Fig.21 In (three-dimensional nanocarbon structure 6), a petal-like structure or a concavo-convex structure can be confirmed in the portion not covered by the carbon binder. Fig. 22 (Three-dimensional shape nanocarbon structure 7) and as an enlarged view Figure 23 to Figure 25 In the figure, it can be clearly confirmed that the petal-like structure and the concavo-convex structure are bonded together by the graphene aggregate as a binder while maintaining their original state. Fig. 22 and Fig.23 This is a low-magnification SEM image. Fig.24 and Fig.25 It is a high-magnification SEM image, especially in Fig.24 and Fig.25 The concave and convex structures can be captured in the image.

[0179] (Neutron transmittance)

[0180] For each sample, the neutron transmittance was measured as follows. That is, neutrons generated by the RIKEN RANS (RIKEN Accelerator-driven Compact Neutron Source) were slowed down by a mesitylene cold neutron moderator and passed through a slit collimator to remove scattered neutrons from the surroundings while converging into a neutron beam with a diameter of 10 mm to irradiate the sample. The sample was attached to the back of a boron carbide (B4C) dispersed rubber mounted on a sample support frame, which was set at a position about 1.5 m away from the surface of the cold neutron moderator. A hole with a diameter of 10 mm was provided in the center of the boron carbide dispersed rubber, and neutrons passing through the hole uniformly passed through the sample. A GEM (Gas Electron Multiplier) detector was set about 100 mm in front of the sample to measure the neutron energy-dependent intensity of the neutron beam that passed through the sample. The neutron energy-dependent transmittance (%) was calculated based on the ratio between the presence of the sample and the absence of the sample. The transmittance was normalized to a per-atom value based on the thickness and density of the sample. All atoms present were carbon. The results are shown in Fig. 27 middle.

[0181] 《Overview of RANS》

[0182] Accelerated ions: protons

[0183] Neutrons undergo nuclear reactions: 9 Be(p,n) 9 B

[0184] Maximum neutron energy: 5MeV

[0185] Acceleration method: RFQ+DTL

[0186] The samples used in the experiment are shown below. The thickness, density and transmittance (%) of these samples at 0.5 meV are shown in Table 4. Fig. 27 The neutron transmittance of each sample when the neutron energy was 0.5 meV was visually read. The results are shown in Table 4.

[0187] Structure 4: Three-dimensional carbon structure 4

[0188] Structure 7: Three-dimensional carbon structure 7

[0189] Graphite: Isotropic graphite manufactured by Toyo Tan Co., Ltd. (bulk density: 1.77 g / cm 3 )

[0190] Nanodiamond: ND plate (ND plate prepared by "M.Teshigawara et Al.(2019).Measurement ofneutron scattering cross section of nano-diamond with particle diameter ofapproximately 5nmin energy range of0.2meV to 100meV.Nuclea Inst.and MethodsPhysics Reserch,A 929,113-120.")

[0191] [Table 4] Table 4

[0192]

[0193] The energy-dependent neutron transmittance curves (profiles) of structure 4 of Example 1 and structure 7 of Example 3 are close to the curve of the nanodiamond of Reference Example 4, and their transmittances are significantly lower than the graphite of Comparative Example 1 (graphite material having the same volume density as the artificial graphite plate of Reference Example 3). This low transmittance is believed to be caused by coherent scattering. Therefore, it is believed that the three-dimensional carbon structure of the embodiment can be used as a reflective material for cold neutrons to increase the intensity of cold neutrons. In addition, by Fig. 27 The energy-dependent neutron transmittance curve of yields the following result: low transmittance can be expected not only for cold neutrons but also for ultracold neutrons.

[0194] Preferred embodiments of the present invention are described below.

[0195] [1] A carbon structure is a three-dimensional carbon structure including a nanocarbon structure, wherein the nanocarbon structure has at least one of a petal-like structure and a concave-convex structure, wherein the petal-like structure is formed by fixing thin flake carbon having a graphene skeleton with a thickness of less than 20 nm into a petal-like shape, and the concave-convex structure is formed by agglomerating seed-like structures with a size of 1 to 100 nm.

[0196] [2] The carbon structure according to [1], wherein the nanocarbon structure has the petal-like structure and the concavo-convex structure.

[0197] [3] The carbon structure according to [1] or [2], further comprising a carbon binder.

[0198] [4] The carbon structure according to [3], wherein the carbon binder contains at least one of thermally expandable graphite and a graphene aggregate.

[0199] [5] The carbon structure according to [3], wherein the carbon binder contains a graphene aggregate.

[0200] [6] The carbon structure according to any one of [1] to [5], wherein the thickness of the carbon structure is 0.1 mm or more.

[0201] [7] The carbon structure according to any one of [1] to [6], wherein the bending strength of the carbon structure is 0.5 MPa or more.

[0202] [8] The carbon structure according to any one of [1] to [7], wherein the bulk density of the carbon structure is 0.70 g / cm 3 above.

[0203] [9] A carbon structure according to any one of [1] to [8], wherein the ratio of the peak intensity of the G band to the peak intensity of the D band obtained by Raman spectroscopy, G / D, is greater than or equal to 3.00, and the ratio of the peak intensity of the G band to the peak intensity of the 2D band, G / 2D, is less than or equal to 3.00.

[0204]

[10] The carbon structure according to any one of [1] to [9], wherein the three-dimensional shape is a plate, a disk, a tube, or a shape of a divided piece obtained by dividing the tube.

[0205]

[11] The carbon structure according to any one of [1] to

[10] , wherein the neutron transmittance of the carbon structure to 0.5 meV neutrons is 80% or less.

[0206] Description of Reference Numerals

[0207] 1Muffle furnace body

[0208] 2. Heat-resistant rubber (for sealing)

[0209] 3. Muffle furnace cover

[0210] 4 screw holes for fixing

[0211] 5 Atmosphere gas inlet

[0212] 6 Atmosphere gas exhaust port

[0213] 7 Cooling water inlet

[0214] 8 Cooling water outlet

Claims

1. A carbon structure having a three-dimensional shape including a nanocarbon structure, The nanocarbon structure has at least one of a petal-like structure and a concave-convex structure. The petal-like structure is formed by fixing thin-sheet carbon with a graphene skeleton and a thickness of less than 20nm into a petal shape, and the concave-convex structure is formed by the aggregation of seed-like structures with a size of 1 to 100nm.

2. The carbon structure according to claim 1, wherein The nanocarbon structure has the petal-shaped structure and the concavo-convex structure.

3. The carbon structure according to claim 1 or 2, wherein A carbon binder is also included.

4. The carbon structure according to claim 3, wherein The carbon binder includes at least one of thermally expandable graphite and a graphene aggregate.

5. The carbon structure according to claim 3, wherein The carbon binder includes a graphene aggregate.

6. The carbon structure according to claim 1 or 2, wherein: The carbon structure has a thickness of 0.1 mm or more.

7. The carbon structure according to claim 1 or 2, wherein: The carbon structure has a bending strength of 0.5 MPa or more.

8. The carbon structure according to claim 1 or 2, wherein: The volume density of the carbon structure is 0.70 g / cm 3 above.

9. The carbon structure according to claim 1 or 2, wherein: The ratio G / D of the peak intensity of the G band to the peak intensity of the D band obtained from the Raman spectrum is 3.00 or more, and the ratio G / 2D of the peak intensity of the G band to the peak intensity of the 2D band is 3.00 or less.

10. The carbon structure according to claim 1 or 2, wherein: The three-dimensional shape is a plate shape, a disk shape, a tube shape, or a shape of a divided piece obtained by dividing the tube shape.

11. The carbon structure according to claim 1 or 2, wherein: The carbon structure has a neutron transmittance of 80% or less for 0.5 meV neutrons.

Citation Information

Patent Citations

  • Carbon material and method for producing same

    WO2011102473A1